A New Century of the Impossible: Giovanni Papini’s "Fantastico Interno" - Reza, M (Johns Hopkins University Press, 2017)
This article firstly investigates Papini’s claim to a new type of fantastic narrative, that of a “fantastico interno” of the mind, as distinct from and reversing a “fantastico esterno” that is characteristic of Edgar Allan Poe and the nineteenth century. Secondly, this article analyzes a small corpus of Papini’s texts in order to see how an “interno” fantastic works in practice. I argue that Papini’s “fantastico interno” does not have as strict a remit as first proposed, and that his model is an attempt to add a new theoretical dimension to understanding fantastic literature at the beginning of the twentieth century.